Acute kidney injury and mortality in critically ill children - Putri Amelia; Munar Lubis; Ema Mutiara; Yunnie Trisnawati (Indonesian Pediatric Society Publishing House, 2014)
Background Mortality from acute kidney injury (AKI) can be as high as 60% in critically ill children. This high mortality rate is influenced by the severity of primary diseases, organ dysfunction, and the stage of acute kidney injury. Objective To assess for an as sedation between AKI and mortality in critically ill children hospitalized in the pediatric intensive care unit (PICU). Methods A cross-sectional study was conducted from April to July 2012. All patients aged 1 month to 18 years who were hospitalized in the PICU for more than 24 hours were included. Urine output and serum creatinine levels were evaluated daily. Patients were categorized according to the pediatric risk, injury, failure, loss, and end stage renal disease (pRIFLE) criteria. Chi square, Fisher's exact, Mann-\X'hitney U, and Kruskal-Wallis tests were used to assess for an association between AKI, mortality, pediatric logistic organ dysfunction (PELOD) score, and length of PICU stay. AP value of < 0.05 was considered as statistically significant. Results During the study period, 57 children were admitted, consisting of 25 (43.9%) females and 32 (56.1 %) males, with a median age of 43 months. The prevalance of AKI was 31.5% (18/57) and classified into stages: risk 13/18, injury 3/18, and failure 2/18. The mortality rate for AKI was 16. 7%. There was no association between AKI and mortality (P=0.592). The PELOD scores were found to be similar among patients (SD 11.3 2 vs. SD 12.23; P=0.830), and there was no association between AKI and length of PICU stay (P=0.819). Conclusion There is no association between AKI and mortality in critically ill children admitted in PICU.